Lightweight generic random ferns for multi‐target augmented reality on mobile devices. Issue 13 (1st June 2013) - Lee, Suwon; Yang, Hyun S.
Abstract : Proposed use lightweight generic random ferns (LGRF), a fast keypoint classifier designed for multi‐target augmented reality (AR) on mobile devices. LGRF uses binary features of image patches for both object recognition and keypoint matching of multiple objects, and stores probabilities in a single bit representation to reduce memory requirements. As a result, LGRF can perform simultaneous object recognition and keypoint matching in real time with low memory consumption, making it suitable for multi‐target AR on mobile devices.